Evaluation and Significance of Mortise Instability in Supination External Rotation Fibula Fractures: A Review Article. (July 2018) - Kwon, John Y.; Cronin, Patrick; Velasco, Brian; Chiodo, Christopher
Evaluation and management of ankle fractures has progressed in parallel to an evolving understanding of ankle stability. While stability of the mortise had historically been attributed to the lateral malleolus, Lauge-Hansen's contributions followed by multiple other investigations increased the emphasis on the significance of medial-sided injury in destabilizing the mortise. As the importance of the deltoid ligament has been elucidated, the means of assessing ligamentous incompetence and the prognostic significance of an unstable mortise continue to be defined. Level of Evidence: Level V, expert opinion.